MAIN STAGES OF TECTONIC ACTIVIZATION OF THE STRUCTURES OF CRYSTALLIC BASE AND SEDIMENTARY COVERING OF THE TERRITORY OF UKRAINE AT POST-KARELIAN AGE - MIKHNYTSKA, T.; RYABENKO , V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Several basic stages characterized by the high saturation of the geological events and high productivity for the mineral resources were distinguished in the history of the geological development of the platform part of Ukraine by the results of these investigations.